Long term impact of a major infrastructure project: the port of Gioia Tauro - Mario Genco; Emanuela Sirtori; Silvia Vignetti (European Regional Science Association (ERSA), 2013)
This paper illustrates the story of the Port of Gioia Tauro, a major infrastructure investment co-financed by the European Regional Development Fund in the period 1994-1998, but whose origin dates back to the beginning of the 1970s. It draws from a recent ex-post evaluation carried out for the European Commission aimed at assessing the long term effects produced by a sample of ten major infrastructures in the Transport and Environment sectors and interpreting the key determinants of the observed performance. The analysis shows an emblematic story of great business success and unexploited potential for local development: the overall assessment of the economic impact of the project is mixed, stressing the multi-faceted dimensions of development plans. Although a significant effect in terms of job creation, the expected long term development effects, in particular in terms of industrial development in the surrounding area, did not materialise despite much effort (and money) being spent to that end. Wider effects of efficiency on the Italian and Mediterranean port system are additional benefits of the project, but they did not materialise at the local level and did not affect the living conditions of the local population. A key determinant of the past, present and even future performance of the port is the governance structure of the port and the broader area of Gioia Tauro (including in particular two industrial zones located close to the port area), which has been always characterised by fragmented actions and lack of coordination and clear political will. The number of actors, poor strategic direction, vested interests at national, regional and local level and, finally, conflicts between local public authorities are responsible for the current state of play and are the main difficulty to be resolved going forward. In addition, the weakness of the overall transport (and more specifically port) strategy at national level has exacerbated the existing governance problems. The paper discusses to what extent factors such as governance, managerial response and social acceptability can be key determinants of long term effects of a large infrastructure project, more than forecasting capacity or project technical design. It also offers a pilot case testing an innovative evaluation exercise combining cost-benefit analysis with qualitative assessment and adopting a long-run perspective (30 years), which extends into both the past and the future, and requires a mix of retrospective and prospective analysis.
Keywords: D61; H54; R58; O12; 330; Cost-benefit analysis; Infrastructures; Cohesion Policy; Regional Development